Screening Procedure for Escherichia coli Mutants Deficient in Ribonuclease I - Kaplan, S. (1973)
Strains of Escherichia coli that possess ribonucleic acid accumulated under relaxed growth conditions show a considerable increase in time before the onset of β-galactosidase inducibility. This time dependency can be related to the presence or absence of ribonuclease I.